AN ANALYSIS OF FIGURATIVE LANGUAGE USED IN THE ALBUM SUBMARINE (2011) ALBUM BY ALEX TURNER - Raden Ahmad Derry Destian, - (Universitas Pendidikan Indonesia, 2023)
Figurative language has become a common element found in poetry or song lyrics. This study aims to identify frequently used figurative language and types of love in the lyrics using Abrams (1999) and Sternberg (1986) theories. To achieve the aims, it drew upon a qualitative method focusing on textual analysis. The data were collected from Alex Turner album entitled Submarine. The findings show that four figurative languages and three types of love were found. Four similes, four metaphors, three personifications, and eight hyperboles were identified. In relation to the notion of love, the study identified one liking, one infatuation, and three empty loves. Thus, the most frequently used figurative language in the song lyrics is hyperbole, and the most dominant type of love is empty love. In this album Alex Turner unravels stories about depression, sadness, heartbreak and falling in love.